Non-invasive Fecal Steroid Measurements for Monitoring the Reproductive Status of a Critically Endangered Yangtze Finless Porpoises (Neophocaena asiaeorientalis asiaeorientalis) - Hao, Yu-jiang; Nabi, Ghulam; Deng, Xiao-Jun; Wang, Ding (Frontiers in Endocrinology, 2019)
Yangtze finless porpoise (Neophocaena asiaeorientalis asiaeorientalis) is a critically endangered freshwater cetacean dwelling in the Yangtze River and its adjoining lakes. Affected mainly by the various anthropogenic activities in this region, its population decreased dramatically in the past two decades. To protect this animal from extinction, captive breeding program is an important way to provide basic knowledge for wild population conservation. Noninvasive fecal steroid radioimmunoassay technique was validated in three captive Yangtze finless porpoises for the first time in this study. The seasonality of one captive male and the reproductive status of two females were investigated by longitudinal monitoring their fecal reproductive steroid hormone metabolites. Pregnancy could be diagnosed by an abrupt increase in fecal progesterone metabolites. In late pregnancy (4 months before birth), a significant decrease of fecal progesterone metabolites was observed, which might be referenced for the expectation of parturition date. Seven estrous cycles were recognized in one breeding season of a non-pregnant female judged by the variation of fecal progesterone metabolite levels. The fecal progesterone metabolite level was proved a reliable and precise indicator for estrus and pregnancy diagnosis.